Making Innovation Visible in Agile: A Practical Guide to Capturing and Scaling What Works - Abu Bakar, Shamsulkhomar (Journal of Project Management Research, 2025)
Innovation often happens on the frontlines of Agile delivery — in stand-ups, retrospectives, and sprint adaptations. Yet in many transformation-heavy organisations, especially within the telecommunications sector, these innovations remain invisible. Teams adapt, but their breakthroughs are undocumented, unvalidated, and unscalable. This white paper introduces the VINE Framework (Value-based Innovation Evaluation) — a lightweight, embedded approach that enables Agile teams to identify, validate, and scale innovation from the ground up. Developed within a large national telco ("The Organization"), VINE was piloted across multiple Agile squads and delivered significant impact: 60–70% innovation replicability, integration of innovation prompts in over 40% of retros, and measurable reductions in rework. Grounded in current research on value capture, innovation governance, and Agile scaling challenges, VINE provides a replicable framework that complements existing Agile cadences without adding administrative burden. For organisations striving to close the gap between transformation ambition and on-the-ground learning, VINE offers a path forward: practical, scalable, and aligned with the rhythm of delivery.